2023
DOI: 10.3390/antiox12020441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects between Tannins Extracted from Different Natural Plants on Growth Performance, Antioxidant Capacity, Immunity, and Intestinal Flora of Broiler Chickens

Abstract: In this study, four plant tannins, including AT (Acacia mearnsii tannin, 68%), CT (Castanea sativa tannin, 60%), QT (Schinopsis lorenzii tannin, 73%) and TT (Caesalpinia spinosa tannin, 50%) were added to broiler diets for 42 days to evaluate and compare their effects on growth performance, antioxidant capacity, immune performance and gut microbiota in broilers. The results showed that the supplementation of five tannins could increase the production of T-AOC, GSH-Px, SOD and CAT and reduce the production of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 90 publications
2
5
0
Order By: Relevance
“…This study found that jejunal pro-inflammatory mediators (IL-8, IL-1β, iNOS, IFN-γ) were significantly upregulated, the anti-inflammatory mediator (IL-10) was significantly downregulated in broilers with the CCP challenge, and these results suggested that CCP-infected broilers elicited an intestinal inflammatory response in the jejunum. In our study, dietary supplementation with 1000 mg/kg TA significantly diminished pro-inflammatory mediators and elevated anti-inflammatory mediators with CCP challenge, consistent with previous studies [ 43 , 44 , 45 ]. These results suggest that dietary supplementation with 1000 mg/kg TA is beneficial in alleviating intestinal inflammatory responses in broilers co-infected with CCP.…”
Section: Discussionsupporting
confidence: 93%
“…This study found that jejunal pro-inflammatory mediators (IL-8, IL-1β, iNOS, IFN-γ) were significantly upregulated, the anti-inflammatory mediator (IL-10) was significantly downregulated in broilers with the CCP challenge, and these results suggested that CCP-infected broilers elicited an intestinal inflammatory response in the jejunum. In our study, dietary supplementation with 1000 mg/kg TA significantly diminished pro-inflammatory mediators and elevated anti-inflammatory mediators with CCP challenge, consistent with previous studies [ 43 , 44 , 45 ]. These results suggest that dietary supplementation with 1000 mg/kg TA is beneficial in alleviating intestinal inflammatory responses in broilers co-infected with CCP.…”
Section: Discussionsupporting
confidence: 93%
“…Our investigation found that the ZnO/HTs treatment preserved the cellular expression and localization of tight junction proteins ZO-1 and OCLN. This finding is consistent with various in vivo and in vitro studies concerning HTs, tannic acid, and other polyphenolic compounds [20,49,50]. Conversely, existing literature on ZnO primarily focuses on nanoparticle formulations, which may induce increased cellular cytotoxicity [51].…”
Section: Discussionsupporting
confidence: 86%
“…The relative abundance of the family Oscillospiraceae increased significantly at 400 g/d FAF feeding dose, and it was the only potential biomarker identified for this treatment group ( Figures 7A , B ). Liu et al (2023) discovered that different tannin sources added to broiler diets had varying effects on Oscillospiraceae, with enrichment observed only in Castanea sativa tannin and Schinopsis lorentzii tannin; these specific tannins degrade various structural carbohydrates and produce butyrate, positively impacting broilers’ liver protection. Furthermore, Aurantii Fructus immaturus flavonoid extract increased the proportion of Oscillospiraceae and ameliorated colitis induced by dextran sulfate sodium in mice ( Chen S-.Y.…”
Section: Discussionmentioning
confidence: 99%